Selection of seismic retrofitting techniques through a multi-criteria methodology and BIM tools to improve transparency - Santa-Cruz S. (2018)
Many public school buildings located in seismic areas were designed with obsolete criteria and built with an improper quality control. Faced with the necessity of mitigating future consequences, retrofitting techniques have been suggested with the purpose of obtaining acceptable seismic performances. The selection of the best reinforcement techniques among all alternatives available is a complex task due to the variety of decision factors that have an influence over the final decision. This task is even more difficult when the current seismic reinforcement guidelines or codes do not propose a rational methodology selection. The objective of this investigation is to propose a methodology that improves the selection of seismic reinforcing techniques with a transparency approach. This methodology consists in identifying the decision-making processes and decision criteria of the multi-criteria methods applied in seismic retrofit projects. One of the decision-making processes is the development of collaborative workshops, on which the decision-makers assemble to value the decision criteria according to certain alternatives. Decision criteria such as cost and time are obtained through the Building Information Modelling (BIM) 3D, 4D, and 5D. The study case is the seismic retrofitting of typical public schools in the city of Lima in which this proposed methodology is applied. Results indicate that the best retrofitting technique is the most industrialized in urban areas. Moreover, the methodology includes transparency as a decision criteria and the use of the multi-criteria method and BIM modelling tools are a solid support for a transparent decision-making.